Construcción y deconstrucción de una experiencia pedagógica en el campo de la investigación formativa en trabajo social (2007)
ABSTRACT: This article is the c;lescription of an investigation experience built with and for social work students in the University of Antioquia, from which it was and is possible to develop a process that could allowe to build academic groups in exploration thematic lines, where reflection and collective construction. could make possible studies in tune with particular contexts and, above all, to generate an investigation process, in which the purpose would be to learn to develop investigation with academic, ethic-political and metodological criteria, proper ofsocial work. All this implicates to get over the concepÚon that comes with students and sorne teachers, who keep considering that the objective of the formative investigation in the last pregrado levels, is just for the fulfilment of the graduation piece of work.